Genetic variation analysis of superior cotton varieties of Gossypium hirsutum through microsatellite markers (International Journal of Plant Biology, 2017)
This study was conducted in order to obtain information on genetic variation in populations rated as superior cotton (Gossypium hirsutum L.) varieties in Balittas Malang, Indonesia. The samples used 10 varieties of cotton Kanesia series and 2 other superior varieties that are LRA 5166 and ISA 205A. Indicators of genetic diversity are the number of alleles per locus, allele frequencies, and heterozygosity values. DNA was isolated from the leaves of 3- week-old seedlings using the CTAB method. Amplification was performed using 5 SSRs primer pairs of the JESPR series. The results showed five microsatellite loci, yielding 12 alleles with a size range of 80–500 bp, with an average number of alleles per locus of 4.60. The average values of heterozygosity of the five loci was high, at 0.71. Based on the number of alleles, allele frequencies and heterozygosity values, the genetic variation sampled in the superior cotton varieties studied here is quite high.